Diversity of Botryosphaeriaceae species associated with canker and dieback of avocado (Persea americana) in Italy - Alberto FIORENZA; Giorgio GUSELLA; Laura VECCHIO; Dalia AIELLO; Giancarlo POLIZZI (Phytopathologia Mediterranea)
Increased branch canker and dieback were observed in commercial avocado (Persea americana) orchards in Sicily, Italy. Surveys were conducted in 2021 and 2022 on 11 orchards to investigate etiology of the disease. Seventy-five plants from four orchards, showing branch canker and dieback, were sampled. Isolations from woody diseased tissues revealed the presence of fungi (Botryosphaeriaceae).  Identification of the isolates was achieved by morphological and multi-loci phylogenetic analyses (Maximum Parsimony and Maximum Likelihood) of the ITS, tef1-α, and tub2 loci. Botryosphaeria dothidea, Lasiodiplodia citricola, Macrophomina phaseolina, Neofusicoccum cryptoaustrale, and Neofusicoccum luteum were identified. Representative isolates collected from the orchards, characterized based on the tub2 locus and identified as N. parvum, were excluded from this study, since this species has already been reported in our territory. Pathogenicity tests were conducted on potted, asymptomatic, 2-year-old avocado trees using mycelial plugs. These tests showed that all the Botryosphaeriaceae species characterized in this study were pathogenic to avocado. This is the first report of L. citricola, M. phaseolina and N. cryptoaustrale causing canker and dieback on avocado trees, and is the first record of these fungi causing branch disease on avocado in Italy.